2013
DOI: 10.1302/0301-620x.95b11.31878
|View full text |Cite
|
Sign up to set email alerts
|

Improving pre-operative planning for complex total hip replacement with a Rapid Prototype model enabling surgical simulation

Abstract: Pre-operative planning for total hip replacement (THR) is challenging in hips with severe acetabular deformities, including those with a hypoplastic acetabulum or severe defects and in the presence of arthrodesis or ankylosis. We evaluated whether a Rapid Prototype (RP) model, which is a life-sized reproduction based on three-dimensional CT scans, can determine the feasibility of THR and provide information about the size and position of the acetabular component in severe acetabular deformities. THR was planne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Similar to our experience, Won et al showed that this technique can reduce the intraoperative complications as described above [17]. 3D models have also been described to be of significant use in acetabular surgery preoperatively when implants require contouring in three planes.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to our experience, Won et al showed that this technique can reduce the intraoperative complications as described above [17]. 3D models have also been described to be of significant use in acetabular surgery preoperatively when implants require contouring in three planes.…”
Section: Discussionsupporting
confidence: 79%
“…No fracture around the acetabulum and the stem were evident. Diagnostics 2019, 9, x FOR PEER REVIEW 2 of 10 of hip surgery [10,11]. Clinical application of 3D digital and printed models has been focused particularly on hip arthroplasty for the development of patient-specific instrumentation (PSI) and custom-made implants [8,12,13].…”
Section: Case Reportmentioning
confidence: 99%
“…The final phase of 3D modeling is represented by rapid prototyping, in which 3D models can be printed in real-life size plastic models. Several authors reported useful application of 3D printed models for preoperative implant templating, sizing and surgical simulation of hip surgery [10,11]. Clinical application of 3D digital and printed models has been focused particularly on hip arthroplasty for the development of patient-specific instrumentation (PSI) and custom-made implants [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] This may involve understanding the fracture patterns, preoperative contouring of plates, as well as planning the trajectory of screws and positioning of plates during trauma surgery, or positioning screws and implants during difficult hip and knee reconstructions. 22,25 Although this technology has been used in the past in various specialties such as cardiothoracic surgery, 24 neurosurgery, 26 orthopedic trauma surgery, 22 spinal surgery, 27 dental surgery, 28 and craniomaxillofacial surgery, 29,30 it is only recently that its role has been evaluated in lower extremity total joint arthroplasty. 25 Won et al, in a study of 21 complex primary total hip arthroplasties, evaluated the accuracy of preoperative planning with simulated models of the patients' anatomy of the pelvis manufactured using additive layering technology.…”
Section: Preoperative Planningmentioning
confidence: 99%
“…22,25 Although this technology has been used in the past in various specialties such as cardiothoracic surgery, 24 neurosurgery, 26 orthopedic trauma surgery, 22 spinal surgery, 27 dental surgery, 28 and craniomaxillofacial surgery, 29,30 it is only recently that its role has been evaluated in lower extremity total joint arthroplasty. 25 Won et al, in a study of 21 complex primary total hip arthroplasties, evaluated the accuracy of preoperative planning with simulated models of the patients' anatomy of the pelvis manufactured using additive layering technology. 25 The authors found that in approximately 81% of cases (n ¼ 17), the acetabulum was sized accurately (within 2 mm of the predicted size).…”
Section: Preoperative Planningmentioning
confidence: 99%